Analisa dynamics of handling kendaraan reverse trike ditinjau dari pergeseran centre of gravity (cg) - Bhanu Putra Bumi; Wibowo .; Raymundus Lullus Lambang G (Jurnal Teknik Mesin Indonesia, 2017)
The purpose of this research is to get the dynamics behavior of the Reverse Trike vehicle handling based on testing and calculation analysis using Newton's first law principle. Reverse Trike has a length of Wheelbase (L) 1.14 m, Trackwidth width (tf) 0.81 m, front wheel suspension (bf), and Ground Clearance 0.11 m. Testing starts from vehicle weighing to get the average weight of the front wheel (Wf), rear wheel weight (Wr), and total vehicle weight (Wt). Then do U-Turn maneuver testing with variations in speed from 20 km / h to 50 km / hour. Calculation analysis is done by considering the Load Transfer that occurs on the vehicle that is doing the maneuver. Braking results in rolling moments, centrifugal force due to vehicle maneuver resulting in pitching moments, and vehicle acceleration results in a drag force. The results showed that Reverse Trike vehicle design experienced Oversteer behavior when performing maneuver motion. This is indicated by the value of Index Understeer (Kus). The average value of Kus at 20 km/h speed is -4.33. At 30 km/h speed is -2.68. At 40 km/h speed is -2.04. And at 50 km/h speed is -1.58.